The development of embedded low-pass filter for vibration control of a flexible manipulator - Aainaa Hazwani, Mohd Hashim (2009)
This project presents an investigation into developing feedforward control scheme for vibration of a flexible manipulator using low pass (IIR) filter technique using Xilinx ISE 10.1 (Spartan 3E). A constraint planar single link flexible manipulator is considered in this project and dynamic model of the system is derived using assumed mode method. A bang-bang torque input signal is used to determine the characteristic parameters for designed and evaluate for vibration control technique. The low pass filter algorithm is designed with sampling frequency of 1000 Hz and cut-off frequency 20 Hz. After that, it is embedded in Field Programmable Gate Array (FPGA) board using Xilinx ISE 10.1 software. This algorithm is then applied to the flexible manipulator in the simulink through PCI 1710 HG DAQ Card. The experimental results presented in time and frequency domain. The effects of the filter order in low pass performance are also investigated. Finally, a simulation of low pass filter , in Matlab is compared in the embedded filter onto FPGA board.